MYBL2 alternative splicing-related genetic variants reduce the risk of triple-negative breast cancer in the Chinese population - Chen, Xinyu; Feng, Jin; Zhang, Yuan; Liu, Jiarui; Zhang, Lijia; Zeng, Pu; Wen, Langbo; Wang, Xin; Zhang, Yi (Frontiers in Genetics, 2023)
Background: Triple-negative breast cancer (TNBC) is the most malignant subtype of breast cancer, and studies have found an association between the Myb proto-oncogene like 2 (MYBL2) gene and TNBC development; however, the specific mechanisms underlying development remain unknown. Recent studies have reported the association of alternative splicing (AS) with cancer, providing new approaches to elucidate the carcinogenesis mechanism. This study aimed to identify MYBL2 AS-related genetic variants that influence the risk of developing TNBC, providing new ideas for probing the mechanism of TNBC and novel biomarkers for TNBC prevention. Methods: We conducted a case-control study of 217 patients with TNBC and 401 cancer-free controls. The CancerSplicingQTL database and HSF software were used to screen for MYBL2 AS-related genetic variants. The association of sample genotypes with the risk of TNBC development and with clinicopathological features was analysed via unconditional logistic regression. Combining multiple platforms, the candidate sites were subjected to biological function analysis. Results: Two AS-associated SNPs, rs285170 and rs405660, were identified using bioinformatics analysis. Logistic regression analysis showed that both rs285170 (OR = 0.541; 95% CI = 0.343–0.852; p = 0.008) and rs405660 (OR = 0.642; 95% CI = 0.469–0.879; p = 0.006) exhibited protective effects against TNBC under the additive model. Stratification analysis showed that these two SNPs had more significant protective effects in the Chinese population aged ≧50 years. Additionally, we found that rs405660 was associated with the risk of lymph node metastasis (OR = 0.396, 95% CI = 0.209–0.750, p = 0.005) in TNBC. Functional analysis revealed that both rs285170 and rs405660 are associated with splicing of exon 3 and that the exon 3-deleted spliceosome does not increase breast cancer risk. Conclusion: We found for the first time that MYBL2 AS-related genetic variants are associated with reduced TNBC susceptibility in the Chinese population, especially in women aged ≧50 years.